2023
DOI: 10.1002/anie.202314312
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Aromatic N‐Heterocyclic Radicals for Functionalization of Unactivated Alkenes

Lu Wang,
Minxu Shi,
Xiaoping Chen
et al.

Abstract: Nitrogen‐centered radicals (NCRs) have been widely recognized as versatile synthetic intermediates for the construction of nitrogen containing molecules of high value. As such, there has been a long‐standing interest in the field of organic synthesis to develop novel nitrogen‐based radicals and explore their inherent reactivity. In this study, we present the generation of aromatic N‐heterocyclic radicals and their application in a novel and diverse functionalization of unactivated alkenes. Bench‐stable aromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…In 2023, the Zhang group documented a novel visible-light induced photoredox-catalyzed hydroamination reaction of unactivated alkenes 165 with pyridinium salt derived aromatic N-heterocyclic radicals (Scheme 24b). 82 In this process, the addition of Lewis acid Fe(OTf) 3 can increase the efficiency of the reaction. Mechanistic investigations showed that the key N-heterocyclic radical intermediate is generated through EnT-based activation of the corresponding pyridinium salt 164 .…”
Section: Iron-involved Metallaphotocatalysismentioning
confidence: 99%
“…In 2023, the Zhang group documented a novel visible-light induced photoredox-catalyzed hydroamination reaction of unactivated alkenes 165 with pyridinium salt derived aromatic N-heterocyclic radicals (Scheme 24b). 82 In this process, the addition of Lewis acid Fe(OTf) 3 can increase the efficiency of the reaction. Mechanistic investigations showed that the key N-heterocyclic radical intermediate is generated through EnT-based activation of the corresponding pyridinium salt 164 .…”
Section: Iron-involved Metallaphotocatalysismentioning
confidence: 99%
“…23 However, N-H azoles have not been reported. Recent work by the groups of Zhang 24 and Chen 25 have demonstrated the feasibility of alkene hydroamination via heterocylic NCRs using N-functionalized azoles, such as N-pyridinium salts and hydroxybenzotriazoles, respectively. Thus, identification of a mild and general strategy for N-H bond activation of azoles could prove highly enabling in the development of this and numerous other reactions that deliver medicinally relevant heterocyclic products.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, N−H azoles have not been reported as competent substrates. Recent work by the groups of Zhang 24 and Chen 25 have demonstrated the feasibility of alkene hydroamination via heterocyclic NCRs using N-functionalized azoles, such as Npyridinium salts and hydroxybenzotriazoles, respectively. Thus, identification of a mild and general strategy for N−H bond activation of azoles could prove highly enabling in the development of this and numerous other reactions that deliver medicinally relevant heterocyclic products.…”
Section: ■ Introductionmentioning
confidence: 99%